The Imparative Of Repositioning Nigeria’s Development Initiative Through Agriculture, The Neglected Path - Okwuwa, Charles Onuora (Advances in Social Sciences Research Journal, 2019)
Through series of age-long interactions and experimentations, agricultural production with its associated technologies, has always been the pivot for rural and general socio-economic development. By implication, at least among the Third World countries, agriculture, among other sectors and depending on how it is managed, addresses poverty and unemployment challenges. Since antiquity, Nigeria has practiced agriculture, yet rising food insecurity, unemployment, poverty and stagnated development prevail. These are reversible with adoption of the UN 2030 Sustainable Development Goals (UN, 2015). The challenge to social science prompted this empirical research in Lapai community with the aim of interrogating Nigeria’s agricultural practices, issues and prospects towards widening fact based knowledge for enhanced and beneficial agricultural production. The research relied on both quantitative and qualitative methods and generated data from famers in the locality. Among the findings are that systemic exclusive governance and associated impunity, waste, and leadership failure, among others, stagnate agricultural production, grow poverty, unemployment and socio-economic development crisis. Respondents identify government and culture as the sources of the country’s failure in agricultural production and related socio-economic problems and also hold the view that these forces should lead the deconstruction of the problem. Respondents view grassroots attention to farmers as key in developing Nigeria. Among the recommendations are strategic inclusiveness of farmers and all stakeholders in agricultural planning and implementation, liberalized extension services to farmers including financing, training, tools and seedlings.